The Conflict Element in Modern and Contemporary Dramaturgy: : tool of analysis and creation - Ricken Lopes de Barros, João Pedro; Olinto, Lidia (Revista Brasileira de Estudos da Presença, 2022)
This article focuses on conflict as a dramaturgical element, with the objective of firstly performing a bibliographic review on this specific theme, besides showing its presence and relevance not only in more traditional dramatic works but also in dramaturgies of greater rupture from the dramatic canon in which epicization and/or lyricism stand out. It also proposes to consider conflict as a tool for analysis and creation based on the system of division into drives (intersubjective, extrasubjective and intrasubjective) and axes (intrafictional and extrafictional) that interchange.